Positive electrode material and preparation method thereof, positive electrode plate and battery

The ternary single crystal material and the ferromanganese lithium iron phosphate positive electrode material prepared through reasonable proportioning and sintering processes solve the problems of poor stability of ternary materials and insufficient conductivity of lithium iron phosphate, and improve the charging and discharging efficiency of lithium-ion batteries and Safety performance.

CN119297266APending Publication Date: 2025-01-10EVE POWER CO LTD

Patent Information

Application Number
CN202411442037.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing ternary materials (NCM) have poor stability and the conductivity of lithium manganese iron phosphate (LMFP) materials is insufficient, which limits the application of lithium-ion batteries in long battery life and fast charging scenarios.

Method used

Using the reasonable ratio of ternary single crystal material and lithium iron manganese phosphate, control its lattice spacing, form a suitable positive electrode material, enhance the stability and conductivity of the material, and mix the nickel-cobalt-manganese hydroxide precursor and lithium source The positive electrode material with excellent electrochemical properties was prepared by sintering the lithium manganese iron phosphate precursor, the phosphate and manganese mixture and the alkali solution.

Benefits of technology

It improves the stability and conductivity of the positive electrode material, improves the charging and discharging efficiency of lithium-ion batteries, and has high energy density and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297266A_ABST
    Figure CN119297266A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode plate and a battery, the positive electrode material comprises a positive electrode active material, and the positive electrode active material comprises a ternary single crystal material and lithium ferric manganese phosphate; the crystal lattice spacing a1 of the crystal of the ternary single crystal material is equal to b1, the range of the crystal lattice spacing a1 is # imgabs 0 #, the range of the crystal lattice spacing c1 is # imgabs 1 #, the crystal lattice spacing a2 of the crystal of the lithium iron manganese phosphate is equal to b2, and the range of the crystal lattice spacing a2 is # imgabs 2 #, and the range of the crystal lattice spacing c2 is # imgabs 3 #. The stability and conductivity of the positive electrode material can be improved, so that the charge-discharge efficiency of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] As an important component of lithium-ion batteries, the choice of positive electrode materials directly affects the performance of lithium-ion batteries, and different positive electrode materials have different advantages and disadvantages due to the structural characteristics of their own materials. At present, in order to take into account the energy density and safety of the battery, it is an emerging method to compound ternary materials (NCM) with lithium iron manganese phosphate (LMFP) materials to combine the advantages of the two materials, achieve complementary shortcomings, and obtain batteries with higher energy density and safer high performance. However, the ternary material (NCM) has poor stability, and the lithium iron manganese phosphate (LMFP) material has the disadvantages of insufficient conductivity. In scenarios with special requirements such as long battery life and fast charging, their applications are seriously affected. Summary of the invention

[0003] The embodiments of the present invention provide a positive electrode material and a preparation method thereof, a positive electrode plate and a battery, which can improve the stability and conductivity of the electrode material and enhance the charge and discharge efficiency of the battery.

[0004] In order to achieve the above-mentioned object, according to a first aspect of the present application, there is provided a positive electrode material, comprising a positive electrode active material, wherein the positive electrode active material comprises a ternary single crystal material and lithium iron manganese phosphate;

[0005] The lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, wherein a1=b1, and the range of a1 is The range of c1 is

[0006] The lattice spacing of the lithium iron manganese phosphate crystal in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, wherein a2=b2, and the range of a2 is The range of c2 is

[0007] The first direction intersects with the second direction, and both the first direction and the second direction are perpendicular to the third direction.

[0008] In some embodiments, in the positive electrode active material, the mass percentage of the ternary single crystal material is M1, and the range of M1 is 10% to 40%; the mass percentage of the lithium iron manganese phosphate is M2, and the range of M2 is 60% to 90%.

[0009] In some embodiments, the ratio of M1, M2, a1, a2, c1 and c2 is: 32<(M1*a1*c1)+(M2*a2*c2)<34.

[0010] In some embodiments, the positive electrode material further includes a conductive agent and a binder;

[0011] Among them, in the positive electrode material, the mass percentage of the positive electrode active material ranges from 94.5% to 97%, the mass percentage of the conductive agent ranges from 1.5% to 3%, and the mass percentage of the binder ranges from 1.5% to 2.5%.

[0012] In some embodiments, the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

[0013] According to a second aspect of the present application, a method for preparing a positive electrode material is provided, comprising:

[0014] A nickel-cobalt-manganese hydroxide precursor, a lithium source and an additive are mixed and sintered to obtain a ternary single crystal material, wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is The first direction intersects the second direction, and both the first direction and the second direction are perpendicular to the third direction;

[0015] A lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution are mixed and sintered to obtain lithium iron manganese phosphate, wherein the lattice spacing of the lithium iron manganese phosphate crystals in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is

[0016] The positive electrode active material is mixed with a conductive agent and a binder to obtain a positive electrode material.

[0017] In some embodiments, the step of mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and an additive and sintering to obtain a ternary single crystal material comprises:

[0018] Mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and a first additive, and performing a first sintering to obtain a ternary single crystal sintered material;

[0019] Then, the ternary single crystal sinter is mixed with a second additive and sintered for a second time to obtain a ternary single crystal material;

[0020] The steps of mixing a lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution and sintering to obtain lithium iron manganese phosphate include:

[0021] In a liquid phase system, a lithium iron manganese phosphate precursor, a phosphorus-manganese mixed solution and an alkaline solution are mixed, dried, and then sintered in an inert gas atmosphere to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

[0022] According to a third aspect of the present application, a positive electrode plate is provided, comprising a positive electrode current collector and the positive electrode material as described in the first aspect coated on the positive electrode current collector.

[0023] In some embodiments, at least one side of the positive electrode current collector is coated with the positive electrode material, and the single-side surface density coated with the positive electrode material is 210 g / m 2 ~230g / m 2 .

[0024] According to a fourth aspect of the present application, a battery is provided, comprising the positive electrode plate as described in the third aspect.

[0025] The present application provides a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. The positive electrode material of the present application includes a positive electrode active material, and the positive electrode active material includes a ternary single crystal material and lithium iron manganese phosphate, wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is The lattice spacing of the lithium iron manganese phosphate crystal in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is The positive electrode active material of the present application is formed by mixing a ternary single crystal material and lithium iron manganese phosphate, and the lattice spacing of the two is controlled within the above range, so that the positive electrode material has a suitable lattice spacing, which helps to accommodate more ions, enhance the stability and conductivity of the positive electrode material, and thus improve the charging and discharging efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0027] Figure 1 is a schematic diagram of the crystal structure of a ternary single crystal material provided in an embodiment of the present application;

[0028] Figure 2 This is a schematic diagram of the crystal structure of lithium iron manganese phosphate provided in an embodiment of the present application;

[0029] Figure 3 This is a flow chart of a method for preparing a positive electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0031] According to a first aspect of the present application, a positive electrode material is provided, the positive electrode material includes a positive electrode active material, the positive electrode active material includes a ternary single crystal material (NCM) and lithium manganese iron phosphate (LMFP). The lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is The lattice spacing of the lithium iron manganese phosphate crystal in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is The first direction intersects with the second direction, and both the first direction and the second direction are perpendicular to the third direction.

[0032] Ternary single crystal materials and lithium iron manganese phosphate both belong to the hexagonal crystal system. The characteristic symmetry of the hexagonal crystal system determines that the basis vectors corresponding to the hexagonal crystal cell are: the two minor axes (a, b) are perpendicular to the major axis (c), the magnitudes of the two minor axis basis vectors are equal, and the angle between the minor axes is 120°, that is, its unit cell parameters have the relationship of a=b≠c, α=β=90°, γ=120°.

[0033] Please refer to Figure 1-Figure 2 , Figure 1 is a schematic diagram of the crystal structure of a ternary single crystal material provided in an embodiment of the present application, Figure 2It is a schematic diagram of the crystal structure of lithium iron manganese phosphate provided by an embodiment of the present application. In the present application, the crystal structure has a first direction a, a second direction b and a third direction c, and the first direction and the second direction are both perpendicular to the third direction. Wherein, a1 represents the lattice spacing of the crystal of the ternary single crystal material in the a direction, b1 represents the lattice spacing of the crystal of the ternary single crystal material in the b direction, c1 represents the lattice spacing of the crystal of the ternary single crystal material in the c direction (perpendicular to the bottom surface direction), a1=b1≠c1; a2 represents the lattice spacing of the crystal of lithium iron manganese phosphate in the a direction, b2 represents the lattice spacing of the crystal of lithium iron manganese phosphate in the b direction, c2 represents the lattice spacing of the crystal of lithium iron manganese phosphate in the c direction (perpendicular to the bottom surface direction), a2=b2≠c2.

[0034] The charging and discharging process of lithium-ion batteries is accompanied by the continuous insertion and extraction of lithium ions. The performance of the electrode material is of great significance to the free and stable insertion and extraction of lithium ions. Among them, the lattice size of the electrode material is an important parameter to measure this ability. If the lattice is too large, the binding force between atoms will be weakened, and it will be easy to deform when subjected to external force, affecting the stability of the material; if the lattice is too small, the distance between atoms will decrease, the scattering of electrons will increase, the resistance to ion diffusion will increase, and the conductivity will decrease, which will increase the polarization of the electrode and reduce the charging and discharging efficiency of the battery.

[0035] The present application mixes a ternary single crystal material and lithium iron manganese phosphate as a positive electrode material, while improving the energy density and safety performance of the battery, by controlling the lattice spacing of the ternary single crystal material and the lattice spacing of the lithium iron manganese phosphate within the above-mentioned range, so as to improve the poor stability of the ternary single crystal material and the insufficient conductivity of the lithium iron manganese phosphate.

[0036] The ternary single crystal material and lithium iron manganese phosphate of the present application have a suitable lattice spacing, which helps the electrode material to accommodate more ions and enhance the stability of the structure. The suitable lattice spacing reduces the diffusion resistance of electrons and ions and increases the electrical conductivity, thereby improving the electrochemical properties of the positive electrode material, enhancing the stability and conductivity of the positive electrode material, and thus helping to improve the charging and discharging efficiency of the battery.

[0037] In the positive electrode active material of the present application, the mass percentage of the ternary single crystal material is M1, and the range of M1 is 10% to 40%; the mass percentage of the lithium iron manganese phosphate is M2, and the range of M2 is 60% to 90%. For example, the proportion of the ternary single crystal material and the lithium iron manganese phosphate in the positive electrode active material can be, but is not limited to: the mass percentage of the ternary single crystal material in the positive electrode active material can be 10%, and the mass percentage of the lithium iron manganese phosphate can be 90%; or the mass percentage of the ternary single crystal material in the positive electrode active material can be 20%, and the mass percentage of the lithium iron manganese phosphate can be 80%; or the mass percentage of the ternary single crystal material in the positive electrode active material can be 30%, and the mass percentage of the lithium iron manganese phosphate can be 70%; or the mass percentage of the ternary single crystal material in the positive electrode active material can be 40%, and the mass percentage of the lithium iron manganese phosphate can be 60%. In the positive electrode active material, when the content of ternary single crystal material is too low or the content of lithium iron manganese phosphate is too high, the conductivity of the battery will be too low, the rate performance will be insufficient, and the kinetics will not be improved to improve the fast charging performance. When the content of ternary single crystal material is too high or the content of lithium iron manganese phosphate is too low, the stability of the positive electrode material will be insufficient, and battery thermal runaway and other problems will easily occur.

[0038] In the present application, the mass percentage M1 of the ternary single crystal material and the mass percentage M2 of the lithium iron manganese phosphate are related to the lattice spacing a1, c1 of the ternary single crystal material and the lattice spacing a2, c2 of the lithium iron manganese phosphate, and the ratio of M1, M2, a1, a2, c1 and c2 is: 32<(M1*a1*c1)+(M2*a2*c2)<34. The calculated value of the ratio relationship (M1*a1*c1)+(M2*a2*c2) is within the range of 32 to 34, so that the ternary single crystal material and the lithium iron manganese phosphate in the positive electrode active material have a suitable mass ratio and a suitable lattice size, so that the material has higher conductivity and stability, and at the same time has higher energy density and safety performance, so that the battery has higher charge and discharge efficiency.

[0039] In the present application, the positive electrode material also includes a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode material, and the binder is used to increase the binding performance of the positive electrode material. In the positive electrode material, the total mass of the positive electrode material is 100%, wherein the mass percentage of the positive electrode active material ranges from 94.5% to 97%, the mass percentage of the conductive agent ranges from 1.5% to 3%, and the mass percentage of the binder ranges from 1.5% to 2.5%. When the content of each component of the positive electrode material is within the above range, it has better electrochemical performance.

[0040] Among them, the conductive agent can be but not limited to one or more of conductive graphite, conductive carbon black, acetylene black, carbon nanotubes, etc., and the binder can be but not limited to one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), etc.

[0041] According to the second aspect of the present application, a method for preparing a positive electrode material is provided. Figure 3 , the preparation method of the positive electrode material comprises:

[0042] A nickel-cobalt-manganese hydroxide precursor, a lithium source and an additive are mixed and sintered to obtain a ternary single crystal material, wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is The first direction intersects the second direction, and both the first direction and the second direction are perpendicular to the third direction;

[0043] A lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution are mixed and sintered to obtain lithium iron manganese phosphate, wherein the lattice spacing of the lithium iron manganese phosphate crystals in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is

[0044] Mixing the ternary single crystal material and the lithium iron manganese phosphate to obtain a positive electrode active material;

[0045] The positive electrode active material is mixed with a conductive agent and a binder to obtain a positive electrode material.

[0046] In some embodiments, the method for preparing the positive electrode material comprises the following steps:

[0047] S1. Preparation of ternary single crystal materials

[0048] Mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and a first additive, and performing a first sintering to obtain a ternary single crystal sintered material;

[0049] Then the ternary single crystal sinter is mixed with the second additive and sintered for the second time to obtain a ternary single crystal material; wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is

[0050] The lithium source may be, but is not limited to, one or more of lithium hydroxide, lithium nitrate, lithium acetate, and the like.

[0051] The first additive may be, but is not limited to, one or more of strontium carbonate, aluminum oxide, zirconium hydroxide, zirconium dioxide, lithium nitrate, magnesium dioxide, niobium oxide, yttrium trioxide, aluminum phosphate, tungsten trioxide, and the like.

[0052] The second additive may be, but is not limited to, one or more of metal fluorides, lithium compounds, silicates, phosphates or oxides.

[0053] The temperature range of the first sintering is 750-900°C, and the time of the first sintering is 20-30 hours; the temperature range of the second sintering is 400-500°C, and the time of the second sintering is 3-10 hours.

[0054] Furthermore, after the second sintering, the method further includes the steps of rolling, jaw crushing, crushing and screening to obtain a ternary single crystal material.

[0055] S2. Preparation of lithium manganese iron phosphate

[0056] In a liquid phase system, a lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution are mixed, dried, and then sintered in an inert gas atmosphere to obtain lithium iron manganese phosphate; wherein the lattice spacing of the lithium iron manganese phosphate crystal in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is

[0057] The drying step includes: obtaining a lithium iron manganese phosphate precursor by spray drying.

[0058] The sintering temperature ranges from 750 to 800°C in an inert gas atmosphere, and the sintering time is from 10 to 15 hours.

[0059] The lithium iron manganese phosphate obtained after sintering in an inert gas atmosphere is carbon-coated lithium iron manganese phosphate.

[0060] S3. Preparation of positive electrode active materials

[0061] The ternary single crystal material obtained in step S1 and the lithium iron manganese phosphate obtained in step S2 are mixed to obtain a positive electrode active material.

[0062] The mass percentage of the ternary single crystal material is M1, and the range of M1 is 10% to 40%; the mass percentage of lithium iron manganese phosphate is M2, and the range of M2 is 60% to 90%. The ratio of M1, M2, a1, a2, c1 and c2 is: 32<(M1*a1*c1)+(M2*a2*c2)<34.

[0063] S4. Preparation of positive electrode materials

[0064] The positive electrode active material obtained in step S3 is dispersed in a solvent with a conductive agent and a binder and mixed to obtain a positive electrode material.

[0065] According to a third aspect of the present application, a positive electrode sheet is provided, comprising a positive electrode current collector and the positive electrode material according to the first aspect coated on the positive electrode current collector.

[0066] In the present application, the material of the positive electrode collector can be a metal, such as aluminum or copper, but not limited thereto, and the positive electrode sheet is formed by coating a mixture slurry formed by the positive electrode material as in the first aspect on the surface of the positive electrode collector, and drying and rolling.

[0067] The positive electrode current collector may be a sheet structure having two opposite surfaces, and at least one side of the positive electrode current collector is coated with a positive electrode material, for example, the positive electrode material may be coated on one of the surfaces of the positive electrode current collector, or on both opposite surfaces of the positive electrode current collector. The single surface density coated with the positive electrode material is 210 g / m 2 ~230g / m 2 When the single-sided surface density is within the above range, the battery has a good endurance. When the surface density is too low, the battery capacity is too small, resulting in insufficient endurance; when the surface density is too high, there is a problem of insufficient dynamics on the one hand, and on the other hand, it will lead to an increase in manufacturing costs.

[0068] According to a fourth aspect of the present application, a battery is provided, comprising a battery housing, an electrolyte, a negative electrode plate, a separator and a positive electrode plate as in the third aspect, located in the battery housing.

[0069] The battery shell has a receiving cavity, in which the negative electrode sheet, the separator, and the positive electrode sheet are stacked in sequence, and the electrolyte is contained in the receiving cavity. The material of the battery shell can be metal, such as steel, aluminum, etc.

[0070] The negative electrode sheet includes a negative electrode current collector and a negative electrode material coated on the negative electrode current collector, and the negative electrode material may include graphite, a conductive agent, a binder, etc. The negative electrode sheet is formed by coating a mixture slurry formed by the negative electrode material on the surface of the negative electrode current collector, drying, and rolling.

[0071] The positive electrode material and the battery of the present application are further described below through specific examples.

[0072] 1. Battery preparation method

[0073] S1. Preparation of ternary single crystal materials:

[0074] S11, mixing nickel cobalt manganese hydroxide precursor (NCM622), lithium hydroxide and strontium carbonate, and sintering for the first time at 800° C. for 24 hours to obtain a ternary single crystal sinter;

[0075] S12, the ternary single crystal sinter obtained in step S11 is mixed with Mn3O4, and a second sintering is performed at a temperature of 450°C for 6 hours, and then rolling, jaw crushing, crushing and screening are performed to obtain a ternary single crystal material, wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is

[0076] S2. Preparation of lithium manganese iron phosphate:

[0077] S21, in a liquid phase system, mixing a lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution, and spray drying to obtain a lithium iron manganese phosphate precursor;

[0078] S22. In an Ar gas protection atmosphere, the lithium iron manganese phosphate precursor obtained in step S21 is sintered at a temperature of 700° C. to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate, wherein the lattice spacing of the lithium iron manganese phosphate crystals in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is

[0079] S3. Preparation of positive electrode active materials:

[0080] The ternary single crystal material obtained in step S1 and the lithium iron manganese phosphate obtained in step S2 are mixed to obtain a positive electrode active material, wherein the mass percentage of the ternary single crystal material is M1, and the range of M1 is 10% to 40%; the mass percentage of the lithium iron manganese phosphate is M2, and the range of M2 is 60% to 90%. The ratio of M1, M2, a1, a2, c1 and c2 is: 32<(M1*a1*c1)+(M2*a2*c2)<34.

[0081] S4. Preparation of positive electrode sheet:

[0082] The positive electrode active material, conductive agent and binder obtained in step S3 are dispersed in N-methylpyrrolidone (NMP) and mixed, and stirred evenly to obtain positive electrode slurry. The positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained through drying, cold pressing and other processes. The positive electrode collector is coated on both sides, and the single-side surface density is 210g / m 2 ~230g / m 2Among them, the conductive agent includes conductive carbon black (SP) and carbon nanotubes (CNT), the binder includes polyvinylidene fluoride (PVDF), and the mass ratio of the positive electrode active material, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 96.5:0.9:0.6:2.

[0083] S5. Preparation of negative electrode sheet:

[0084] The negative electrode material, conductive agent and binder are dispersed in a solvent, stirred evenly to obtain a slurry, coated on the negative electrode current collector, and then dried, cold pressed and other processes to obtain a negative electrode sheet. The negative electrode material is graphite, the conductive agent includes conductive carbon black (SP), the binder includes sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR), and the mass ratio of the negative electrode material, conductive carbon black, sodium carboxymethyl cellulose and styrene butadiene rubber is 95.5:2:0.5:2.

[0085] S6. Preparation of battery:

[0086] The vacuum-dried positive electrode sheets, separators and negative electrode sheets are assembled and then cut, die-cut, striped and placed in the battery casing. The electrolyte is then injected under high temperature and negative pressure to assemble into a square aluminum shell battery.

[0087] The batteries of Example 1 and Comparative Examples 1 to 6 were prepared by the above-mentioned battery preparation method. The preparation methods of the positive electrode sheets, negative electrode sheets and batteries of Example 1 and Comparative Examples 1 to 6 are the same, and the only difference is that the lattice spacing and mass percentage of the ternary single crystal material and lithium iron manganese phosphate in the positive electrode active material are different.

[0088] Embodiment 1:

[0089] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 20%, and the mass percentage of the lithium iron manganese phosphate is 80%.

[0090] Comparative Example 1:

[0091] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 20%, and the mass percentage of the lithium iron manganese phosphate is 80%.

[0092] Comparative Example 2:

[0093] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 20%, and the mass percentage of the lithium iron manganese phosphate is 80%.

[0094] Comparative Example 3:

[0095] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 20%, and the mass percentage of the lithium iron manganese phosphate is 80%.

[0096] Comparative Example 4:

[0097] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 20%, and the mass percentage of the lithium iron manganese phosphate is 80%.

[0098] Comparative Example 5:

[0099] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 5%, and the mass percentage of the lithium iron manganese phosphate is 95%.

[0100] Comparative Example 6:

[0101] The lattice spacing a1 of the ternary single crystal material in the positive electrode is c1 is The lattice spacing a2 of lithium iron manganese phosphate is c2 is The mass percentage of the ternary single crystal material in the positive electrode active material is 45%, and the mass percentage of the lithium iron manganese phosphate is 55%.

[0102] 2. Method for determining lattice spacing

[0103] The lattice spacing of the above-mentioned ternary single crystal material and lithium iron manganese phosphate is measured by X-ray diffraction (XRD) method. The steps of measuring the lattice spacing by X-ray diffraction (XRD) method include:

[0104] 1) Sample preparation: Grind the sample into uniform fine particles;

[0105] 2) Test steps: Place the sample on a suitable position on the sample stage with a specific glass slide, then set the wavelength of the X-ray (usually using a copper target), the scanning range (based on the understanding of the material, try to cover the angles where diffraction peaks may appear), and the scanning speed; and make test records;

[0106] 3) Data processing: According to the diffraction pattern obtained from the test, identify each diffraction peak, and according to the Bragg equation 2dsinθ=ηλ (where d is the lattice spacing, θ is the diffraction angle, η is the diffraction order, and λ is the X-ray wavelength), if the wavelength and diffraction angle are known, for a specific diffraction peak (usually high-angle peaks are more accurately calculated) and its corresponding diffraction order (generally simple crystal structures often use first-order diffraction η=1), calculate the crystal plane spacing d.

[0107] It should be noted that if Figure 1-Figure 2 As shown in the figure, ternary single crystal materials and lithium iron manganese phosphate belong to the hexagonal system. In the hexagonal system, there is a relationship: a = b ≠ c, α = β = 90°, γ = 120°. Among them, a and b represent the intraaxial spacing of the lattice plane, and c represents the interlayer spacing of the lattice. For (hkl) crystal planes, such as (100), (001), etc., the relationship between the crystal plane spacing d and the lattice parameter is l / d 2 =4 / 3(h 2 +hk+k 2 / a 2 )+l 2 / c 2 , the values ​​of a, b, and c can be obtained through measurement and calculation.

[0108] In the present application, the lattice spacing a1, c1 of the ternary single crystal material and the lattice spacing a2, c2 of the lithium iron manganese phosphate are measured by the above-mentioned X-ray diffraction (XRD) method, and the measurement results are shown in Table 1.

[0109] 3. Battery performance test

[0110] 1) Rate performance test:

[0111] Example 1 and Comparative Examples 1 to Comparative Examples 6 were capacity-calibrated at 1C at 25°C, and discharged at a 2C rate after being fully charged to test their respective discharge capacity retention rates. The test results are shown in Table 1.

[0112] 2) Cycle performance test:

[0113] After Example 1 and Comparative Examples 1 to Comparative Examples 6 were left at 25°C for 1 hour, they were charged to 4.2V at 1C constant current and constant voltage, with a cut-off current of 0.05C; then they were left for 30 minutes and left at 1C constant current to 2.5V; after 500 cycles, the stability of the material was evaluated by the cycle capacity retention rate. The test results are shown in Table 1.

[0114] 3) Thermal stability test:

[0115] The battery cells of Example 1 and Comparative Examples 1 to 6 were charged to 100% SOC, then overcharged with a 1C current to trigger thermal runaway, and charging was stopped and observed for 1 hour. The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] The ratio relationship in Table 1 represents the calculated value of (M1*a1*c1)+(M2*a2*c2).

[0119] From the data of Example 1 and Comparative Examples 1 to 4, it can be seen that: the NCM lattice spacing and LMFP lattice spacing of Example 1 are within the above-mentioned lattice spacing range of the present application, and the NCM lattice spacing and / or LMFP lattice spacing of Comparative Examples 1 to 4 are not within the above-mentioned lattice spacing range of the present application. Compared with Example 1, the NCM lattice of Comparative Example 1 is reduced, the NCM lattice of Comparative Example 2 is increased, the LMFP lattice of Comparative Example 3 is reduced, and the LMFP lattice of Comparative Example 4 is increased. From the rate performance and cycle performance data of Comparative Examples 1 to 4, it can be seen that when the lattice spacing of Comparative Examples 1 to 4 is not within the above-mentioned lattice spacing range of the present application, its electrochemical performance will deteriorate. The reason is that when the lattice spacing of the positive electrode active material increases, the diffusion resistance of ions and electrons becomes smaller, and the rate performance is improved, but the bonding force between atoms becomes weaker, the stability of the material will deteriorate, and the cycle performance is affected.

[0120] From the data of Example 1 and Comparative Examples 5 to 6, it can be seen that when the mass percentage of NCM and the mass percentage of LMFP are not within the above-mentioned ratio range of the present application, the comprehensive performance of the lithium-ion battery cannot reach the best. When the content of NCM is too low, the rate performance of the battery will be insufficient; when the content of NCM is too high, the large lattice will dominate, which will make the positive electrode material unstable and prone to thermal runaway.

[0121] Therefore, when the positive electrode active material includes a ternary single crystal material and lithium iron manganese phosphate, and the range of the lattice spacing a1 of the crystal of the ternary single crystal material in the first direction is The range of the lattice spacing c1 in the third direction is The range of the lattice spacing a2 of the lithium iron manganese phosphate crystal in the first direction is The range of the lattice spacing c2 in the third direction is At the same time, it can effectively improve the stability and conductivity of the positive electrode material and improve the charging and discharging efficiency of the battery.

[0122] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0123] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.

[0124] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A positive electrode material, characterized in that: The invention comprises a positive electrode active material, wherein the positive electrode active material comprises a ternary single crystal material and lithium iron manganese phosphate; The lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, wherein a1=b1, and the range of a1 is The range of c1 is The lattice spacing of the lithium iron manganese phosphate crystal in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, wherein a2=b2, and the range of a2 is The range of c2 is The first direction intersects with the second direction, and both the first direction and the second direction are perpendicular to the third direction.

2. The positive electrode material according to claim 1, characterized in that In the positive electrode active material, the mass percentage of the ternary single crystal material is M1, and the range of M1 is 10% to 40%; The mass percentage of the lithium iron manganese phosphate is M2, and the range of M2 is 60% to 90%.

3. The positive electrode material according to claim 2, characterized in that The ratio of M1, M2, a1, a2, c1 and c2 is: 32<(M1*a1*c1)+(M2*a2*c2)<34.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The positive electrode material also includes a conductive agent and a binder; Among them, in the positive electrode material, the mass percentage of the positive electrode active material ranges from 94.5% to 97%, the mass percentage of the conductive agent ranges from 1.5% to 3%, and the mass percentage of the binder ranges from 1.5% to 2.5%.

5. The positive electrode material according to any one of claims 1 to 3, characterized in that The lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

6. A method for preparing a positive electrode material, characterized in that: include: A nickel-cobalt-manganese hydroxide precursor, a lithium source and an additive are mixed and sintered to obtain a ternary single crystal material, wherein the lattice spacing of the crystal of the ternary single crystal material in the first direction is a1, the lattice spacing in the second direction is b1, and the lattice spacing in the third direction is c1, a1=b1, and the range of a1 is The range of c1 is The first direction intersects the second direction, and both the first direction and the second direction are perpendicular to the third direction; A lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution are mixed and sintered to obtain lithium iron manganese phosphate, wherein the lattice spacing of the lithium iron manganese phosphate crystals in the first direction is a2, the lattice spacing in the second direction is b2, and the lattice spacing in the third direction is c2, a2=b2, and the range of a2 is The range of c2 is Mixing the ternary single crystal material and the lithium iron manganese phosphate to obtain a positive electrode active material; The positive electrode active material is mixed with a conductive agent and a binder to obtain a positive electrode material.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The step of mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and an additive and sintering to obtain a ternary single crystal material comprises: Mixing a nickel-cobalt-manganese hydroxide precursor, a lithium source and a first additive, and performing a first sintering to obtain a ternary single crystal sintered material; Then, the ternary single crystal sinter is mixed with a second additive and sintered for a second time to obtain a ternary single crystal material; The steps of mixing a lithium iron manganese phosphate precursor, a phosphorus manganese mixed solution and an alkaline solution and sintering to obtain lithium iron manganese phosphate include: In a liquid phase system, a lithium iron manganese phosphate precursor, a phosphorus-manganese mixed solution and an alkaline solution are mixed, dried, and then sintered in an inert gas atmosphere to obtain lithium iron manganese phosphate, wherein the lithium iron manganese phosphate is carbon-coated lithium iron manganese phosphate.

8. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and the positive electrode material according to any one of claims 1 to 5 coated on the positive electrode current collector.

9. The positive electrode sheet according to claim 8, characterized in that: At least one side of the positive electrode current collector is coated with the positive electrode material, and the single-side surface density coated with the positive electrode material is 210 g / m 2 ~230g / m 2 .

10. A battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate type material and preparation method therefor, battery paste, positive electrode, and lithium battery

    CN106935851A

  • Lithium manganese iron phosphate composite material and preparation method thereof

    CN117558883A

Cited By

  • Positive electrode material and preparation method therefor, positive electrode sheet, and battery

    EP4773238A1

  • Positive electrode material and preparation method therefor, positive electrode sheet, and battery

    WO2026081307A1